Humidifier disinfectant, sodium dichloroisocyanurate (NaDCC): assessment of respiratory effects to protect workers’ health - DongSeok Seo; Yong-Hoon Lee; JiMin Jo (Scientific Reports, 2021)
Abstract In South Korea, it has been found that biocides used to control and eliminate harmful organisms are used as humidifier disinfectants and cause lung disease in users. Hence, efforts have been focused on studying the toxicity of biocides in workers who handle them. The purpose of this study was to evaluate the effects of inhalation exposure to sodium dichloroisocyanurate (NaDCC) to protect the health of workers handling NaDCC. F344 rats were exposed to 0.8-, 4-, and 20-mg/m3 of NaDCC for 6 h per day, 5 days per week for 14 days, and the recovery period after exposure was 14 days. In the 20-mg/m3-exposure group, we observed a decrease in food intake in females, a weight loss in males, and a decrease in partially active thromboplastin time in males and females 2 weeks after exposure. We noted a decrease in white blood cells in males in the 4- and 20-mg/m3-exposed groups. Both males and females in the 20-mg/m3 group and males in the 4-mg/m3 group showed irritation in the larynx related to test substance exposure. However, these findings were not observed in the recovery group. The main target organs affected by repeated 2-week inhalation exposure to NaDCC were the nasal cavity and larynx in the upper respiratory tract. The No Observed Adverse Effect Level (NOAEL) was considered to be 0.8 mg/m3 because effects related to NaDCC exposure were observed even at of 4 mg/m3, and these effects were found to be reversible.